Does risk management increases the firm value? : evidence from the jet fuel hedging in the airline industry - Henriques, Ana Maria Alves Joaquim (2015)
This thesis examines the use of financial instruments to hedge jet fuel risk in the airline industry during 2000-2014. The main goals are to understand if changes in the hedging policy increases the airline firm's value, measure by the Tobin's Q and if the use of different financial tools also has an impact in the airline company's value. The results show that all the values are statistically insignificant. This leads to the conclusion that the model used may not be the right one. Further research is needed in the area and maybe the best approach is the one followed by Viessmann (2010).